The corporate investment channel of monetary policy in Denmark - Simone Maria Bonin; Dominic Cucic; Andreas Kuchler; Alexander Meldgaard Otte (Danmarks Nationalbank, 2024)
An important monetary transmission channel works through the impact of interest rate changes on non-financial firms' investment decisions. Higher monetary policy rates affect firms' investment decisions by raising the costs of external financing and lowering aggregate demand for goods and services. Using 20 years of firmlevel data from Denmark, we find that an increase in monetary policy rates is associated with a reduction in corporate investment, particularly by smaller firms.
Keywords: 330; Investment; Monetary policy transmission; Monetary policy; Denmark; Investition; Geldpolitische Transmission; Geldpolitik; Dänemark